Profesionalisme Seorang Guru Dalam Proses Pembelajaran - M Reza Zakaria (edujavare, 2025)
As professional educators, teachers must not only do their work professionally, but they must also have professional knowledge and skills to improve the quality of education. The professionalism of teachers is necessary in the educational process of teaching because the teacher is the key to the success of the teaching learning process. A teacher can be called a professional when he has the following four competences: Pedagogical competence, profecional competence, Social competence and Personality competence. This research aims to understand the professionalism of a teacher and to find out how to implement teacher professionalism in learning. With qualitative research methods, that is, an approach that produces descriptive data of written words. Library research is research in which data is collected by gathering data from various literature. The result of this study is that the professionalism of the teacher can be seen through the ability of a teacher to fulfil his responsibilities as an educator and teacher, including planning, implementing, and evaluating learning outcomes using the competence he possesses.